Problem-Based Learning in Human Growth & Development Counselor Education - Javier F. Casado Pérez Ph.D. NCC; Elliot Witherspoon LPC (Teaching and Supervision in Counseling, 2019)
As a core curricular standard that applies to all Council for the Accreditation of Counseling and Related Educational Programs (CACREP, 2015) accredited programs, human growth and development can present unique challenges for the teaching professional. In this article, we present an in-class activity grounded in problem-based learning that uniquely lends itself to the task of supporting medium-to-large classrooms in learning about human growth and development.
Keywords: problem-based learning; human development; counselor education; teaching and learning